PENGARUH REPUTASI, KUALITAS RELASIONAL DAN KEPERCAYAAN PASIEN TERHADAP KEPUASAN DAN LOYALITAS PASIEN (STUDI KASUS PADA PASIEN RAWAT JALAN BPJS DI RUMAH SAKIT SWASTA KOTA TANGERANG) - Eneng Wiliana; Lena Erdawati; Yanthi Meitry (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2019)
Current government policy requires all hospitals to collaborate with BPJS. The phenomenon that often occurs in some hospitals, is the difference in services between BPJS and non BPJS patients. The purpose of this study was to determine and analyze the effect of reputation, relational quality and trust on BPJS patient satisfaction and loyalty in private hospitals in the city of Tangerang, both partially and simultaneously. And to find out and analyze the effect of satisfaction on BPJS patient loyalty in private hospitals in the city of Tangerang. The research method used is causal research used to prove the cause and effect relationship of several variables. Data collection techniques used were the method of observation, interviews and questionnaires relating to reputation, relational quality, trust in customer satisfaction and customer loyalty. Where the sample used was outpatients in 3 (three) Private Hospitals that have performed BPJS services with well. The analysis technique used is Path Analysis. The results of the analysis show reputation, relational quality, trust affect patient satisfaction and loyalty both partially and simultaneously. And satisfaction affects the loyalty of BPJS outpatients in three private hospitals in the city of Tangerang.